2014
DOI: 10.3390/ijms15058473
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis ABA Receptor RCAR1/PYL9 Interacts with an R2R3-Type MYB Transcription Factor, AtMYB44

Abstract: Abscisic acid (ABA) signaling plays important roles in plant growth, development and adaptation to various stresses. RCAR1/PYL9 has been known as a cytoplasm and nuclear ABA receptor in Arabidopsis. To obtain further insight into the regulatory mechanism of RCAR1/PYL9, a yeast two-hybrid approach was performed to screen for RCAR1/PYL9-interacting proteins and an R2R3-type MYB transcription factor, AtMYB44, was identified. The interaction between RCAR1/PYL9 and AtMYB44 was further confirmed by glutathione S-tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 43 publications
0
33
2
Order By: Relevance
“…MYB44 overexpression in Arabidopsis mutants increases drought tolerance by modifying the regulation of stomatal closure (Jung et al, 2008). However, MYB44 also negatively regulates ABA responses (Jaradat et al, 2013;Li et al, 2014) involved in stomatal closure, leaf senescence, and ROS scavenging (Persak and Pitzschke, 2014). In our study, MYB44 expression correlated positively with glycerol levels and negatively with the expression of NOGC1, a nitric oxide-dependent guanylyl cyclase involved in stomatal closure via Ca 2+ signaling (Mulaudzi et al, 2011;Joudoi et al, 2013).…”
Section: Effects Of O 3 Stress On Photosynthesis and Stomatal Regulationmentioning
confidence: 50%
“…MYB44 overexpression in Arabidopsis mutants increases drought tolerance by modifying the regulation of stomatal closure (Jung et al, 2008). However, MYB44 also negatively regulates ABA responses (Jaradat et al, 2013;Li et al, 2014) involved in stomatal closure, leaf senescence, and ROS scavenging (Persak and Pitzschke, 2014). In our study, MYB44 expression correlated positively with glycerol levels and negatively with the expression of NOGC1, a nitric oxide-dependent guanylyl cyclase involved in stomatal closure via Ca 2+ signaling (Mulaudzi et al, 2011;Joudoi et al, 2013).…”
Section: Effects Of O 3 Stress On Photosynthesis and Stomatal Regulationmentioning
confidence: 50%
“…Interestingly, the ABA receptor, PYL8, was shown to physically interact with both MYB77 and MYB44 and to promote auxinresponsive transcription by MYB77 (Zhao et al, 2014). MYB44 has also been implicated in ABA signaling through direct interaction with an additional ABA receptor, PYL9 (Li et al, 2014), as well as repression of jasmonic acid (JA)-responsive transcription (Jung et al, 2010). These factors have additionally been implicated in salicylic acid (SA) and ethylene signaling (Yanhui et al, 2006;Shim et al, 2013).…”
Section: Identification Of a New Regulatory Module In The Root Hair Cmentioning
confidence: 99%
“…An Arabidopsis R2R3-type MYB gene well characterized for its role in the response to different abiotic and biotic stresses is AtMYB44 / AtMYBR1 [ 32 , 70 , 71 , 72 , 73 , 147 , 148 , 149 ]. As already mentioned in Section 2.3 , the overexpression of this TF in Arabidopsis enhances stomatal closure with the consequent increased drought and salinity tolerance of these transgenics compared to wild type and atmyb44 mutant plants [ 32 ].…”
Section: Crosstalk Among Different Stress Responsesmentioning
confidence: 99%
“…Similar microarray results were reported in both papers [ 32 , 72 ], showing that many well-known positive effectors or regulators of stress responses were similarly down-regulated in AtMYB44-overexpressors compared to wild type plants [ 32 , 72 ]. Recently, it was shown that AtMYB44 competes with ABI1 phosphatase, a negative regulator of ABA signaling, for the binding to the RCAR1/PYL9 ABA receptor [ 73 ]. The proposed model suggested that, upon ABA perception, AtMYB44 competes with ABI1 for binding to RCAR1/PYL9, releasing the inhibitory effect of RCAR1/PYL9 on ABI1 activity and thus down-regulating the expression of ABA-responsive genes [ 73 ].…”
Section: Crosstalk Among Different Stress Responsesmentioning
confidence: 99%